Memahami Etika Bisnis Islam dalam Manajemen Keuangan Serta Konsep Konsep Manajemen Keuangan dalam Islam - Labaika, Sindi; Adhilla, Fitroh; Riduwan, Riduwan (Fakultas Syariah INSURI Ponorogo, 2023)
Ethics is the science that discusses the good and bad actions of human beings as far as the human mind can understand. Ethics in finance talks about financial behavior or activities that are ethically right or wrong. Islamic financial mechanisms run by financial institutions cannot be separated from sharia concepts that regulate product mechanisms and operations. The purpose of this study is to provide an explanation of what are the concepts of finance in Islam. In this research, the type of research we use is qualitative research with a descriptive approach through library research, which is a way of systematically analyzing existing literature such as articles, books, journals and documents related to the research theme and the author uses primary data sources in the form of al-Qur'an and hadith. Islamic financial management in this case the author concludes that in the Islamic treasures, the Qur'an and hadith should be used as the main source in all life activities. Likewise in financial management which is a very sensitive matter in an organization. Similarly, financial management is a very sensitive matter in an organization, especially in educational institutions. Thus, financial management must be organized as much as possible. Maximum financial management does not only depend on how to manage the finances.